Factors Associated With the Do-Not-Resuscitate Decision Among Surrogates of Elderly Residents at a Nursing Home in Taiwan - Yi-Ping Tseng; Lian-Hua Huang; Tzu-Hsin Huang; Li-Ling Hsu; Suh-Ing Hsieh (International Journal of Gerontology, 2017)
Background: Do-not-resuscitate (DNR) in nursing homes is an emerging advance directive in Taiwan, but little research has been conducted. The purpose was to determine the factors associated with signing a DNR directive in the largest hospital affiliated nursing home in Taiwan. Methods: A cross-sectional survey was conducted using a convenience sample from a nursing home in northern Taiwan between January 2011 and January 2012. The demographic characteristics of elderly residents were collected. 213 family surrogates of elderly residents were interviewed using a self-developed structured questionnaire related to DNR issues. The data were analyzed via descriptive statistics and logistic regression analysis. Results: Only 24/213 (11.3%) of elderly residents had the DNR directives. Of these, 20/24 (83%) were made by family surrogates. The factors significantly associated with the DNR decision included the elderly residents had severe brain injury (OR: 8.83, p = 0.023), pulmonary disease (OR: 7.24, p = 0.004), cancer (OR: 5.20, p = 0.045); the family surrogates believe in Buddhism (OR: 8.02, p = 0.030), and ever having discussed DNR with the resident (OR: 19.23, p < 0.001). This model explained 49.4% of the variance in whether or not a resident had a DNR directive. Conclusions: The findings indicated the DNR decision was associated with residents' conditions and surrogates' factors. These information are helpful to medical personnel in nursing homes to better understand and to assist the DNR decision-making process.